Language Acquisition on 2 Years Old Child: Taqiyya Mahiroh Case - Fitri Randia Ningsih; Sholihatul Hamidah Daulay (ELITE JOURNAL, 2023)
ABSTRACT In this discussion, the researcher would like to explain how a child acquires his first language. The first language is the language that is acquired when a child is born. The first language is the language that is learned first in everyday life. The study aims to examine how a child learns his or her first language. The author would like to know about the first sentence a child says, and what are the problems with children learning with their first language. In this discussion, the researcher wants to present the results of research on growth and development on children 2 years old, especially in the development of speech style, speech, etc, and to know how about first language on a two years old child “Taqiyya Mahiroh” language development. In this study, the researcher uses a qualitative approach. Researchers conducted research by observing and recording children, how the activities and ways of communicating the child around her are the main objectives in this study. This study was conducted for approximately 3 weeks at Taqiyya's house in Medan. After all data has been obtained by observation and recording, the researcher will define the basic meaning of analytical research on morphology, phonology, syntax, and discourse. Based on research, Taqiyya acquires her first language and develops her language quickly, due to biological and environmental factors, parents and people around her always invite her to talk and communicate. Therefore, Taqiyya can communicate with other people well and quickly. On the other hand, environmental factors and parents are very important supporter in the development of a child first language. Keywords no: First language, child, acquired, acquisition